Exercise and work performance: physical health, workplace communication competency, and perceived team cohesion as mediators - Lau, Ruo Shin (2021)
Exercising has shown to have positive spillover to the workplace where employees reported better work performance, physical health, and group dynamics. Nevertheless, the current literature has predominantly focus on the benefits of exercising, which types of exercises (i.e., individual exercise and team exercise) were rarely distinguished, and the underlying process was yet unclear. Drawing on social learning and conservation of resource theory, the study proposed that team exercise, individual exercise, and no exercise spilled over onto employees’ work performance differently. Furthermore, physical health, workplace communication competency, and perceived team cohesion were proposed as mediators for the relationship between exercise and work performance. Participants consisted of 277 working adults (48% females; 52% males) belonging to three groups: team exercise (n= 74), individual exercise (n= 81), and no exercise (n= 122). Participants’ self-reported data were collected via online survey. Hayes’s PROCESS was used to test the proposed mediation model which workplace communication competency emerged as a significant positive mediator for team exercise. This suggests positive spillover of communication skills and knowledge from team exercise to employee’s work performance. Besides that, team exercise was most likely to improve employee’s work performance, physical health, workplace communication competency, and perceived team cohesion. Theoretical and practical implications of current findings were discussed in which may facilitate employees’ work performance by exercising.